The Relationship Between Paucibacillary Type Leprosy and The Success of Leprosy Treatment in East Java - Mayam Tami (Jurnal Berkala Epidemiologi, 2019)
Background: Indonesia is the third highest contributor to leprosy in the world. The prevalence of Pausi Basiler (PB) type leprosy in East Java has increased from 2015-2017, but the success rate of treatment is more common in PB leprosy compared to Multi Basiler leprosy (MB). Purpose: This study aimed to analyze the relationship between the numbers of PB type leprosy incidence with the success rate of leprosy treatment in East Java in 2015-2017. Methods: This study was an observational analytic study with cross-sectional design. The population used is leprosy patients who have successfully treated by leprosy therapy in East Java which was recorded from 2015 to 2017. The population sampling technique was performed in this study. Moreover, univariate and bivariate analysis were used. Specifically, Spearman correlation test was part of bivariate analysis. Results: This study showed the success presentation of leprosy treatment in male patients has increased for three consecutive years, namely 59.07% in 2015, 59.74% in 2016, and 63.96% in 2017. Oppositely, the success rate of leprosy in the female group decreased each year. There is a significant relationship between the number of PB type leprosy cases with the success rate of leprosy treatment in East Java from 2015 to 2017 (p= 0.00; p <0.05; Spearman correlation = 0.89). Conclusion: The highest success rate of leprosy treatment found in the male group. There is a relationship between the numbers of PB type leprosy cases with the success rate of leprosy treatment in East Java from 2015 to 2017.